2011
DOI: 10.1190/1.3567265
|View full text |Cite
|
Sign up to set email alerts
|

Understanding geophysical responses of shale-gas plays

Abstract: Unconventional resources such as shale gas are becoming increasingly important exploration and production targets. To understand the geophysical responses of shale-gas plays, we use a rock physics relationship, which is constrained with geology and formation-evaluation analysis, to calculate effective properties such as impedance and [Formula: see text]. Numerical studies suggest that in-situ rock para-meters such as mineral composition (e.g., clay, quartz, and calcite) and TOC, as well as the interaction amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…Brittle minerals are essential for hydraulic fracturing (Bower, 2007;Montgomery et al, 2005;Jarvie et al, 2007;Mathews et al, 2007;Zhu et al, 2011). In this study, we found that the silicates (Quartz þ feldspar) content also has a positive correlation with gas content (Fig.…”
Section: The Correlation Between Gas Content and Silicates (Quartz þ mentioning
confidence: 60%
See 1 more Smart Citation
“…Brittle minerals are essential for hydraulic fracturing (Bower, 2007;Montgomery et al, 2005;Jarvie et al, 2007;Mathews et al, 2007;Zhu et al, 2011). In this study, we found that the silicates (Quartz þ feldspar) content also has a positive correlation with gas content (Fig.…”
Section: The Correlation Between Gas Content and Silicates (Quartz þ mentioning
confidence: 60%
“…Higher porosity can provide much more volume for shale gas, that's why silicates have a positive correlation with gas content within the Lower Silurian Longmaxi shale in this study. Many studies also found that it is easier to fracture the shale interval with the shale having a relatively high content of brittle minerals to release more shale gas (Bower, 2007;Montgomery et al, 2005;Jarvie et al, 2007;Mathews et al, 2007;Zhu et al, 2011). The organic and brittle minerals-rich shale interval with high gas content is pay zone from both perspectives of reservoir and completion quality.…”
Section: The Correlation Between Gas Content and Silicates (Quartz þ mentioning
confidence: 93%
“…It is challenging to characterise unconventional natural gas reservoirs, because the elastic properties of shale rock vary significantly within and across such reservoirs due to various mineral composition and fabric anisotropy parameters exhibited by these organic rich shales (Altowairqi et al, 2015;Zhu et al, 2011). Presently our understanding of their dynamic and elastic behaviour is very limited, due to the low volume of variable organic shale samples available as well as the amount of time taken to test low-permeability samples.…”
Section: Introductionmentioning
confidence: 98%
“…Although the well logs response of the gas-bearing shale is complicated, shale gas reservoir has obviously characteristics in the conventional well logging curves [31][32][33][34][35][36][37]. Concretely, both GR and resistivity are all high.…”
Section: Well Logs Responsementioning
confidence: 99%